Impact of social support on the work performance in digital services professionals: the mediating role of work engagement - Petiz Lousã , Eva (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
The world of work is fast changing as a result of digitalization. Particularly post-COVID-19, remote (teleworking) and digital work platforms have grown, increasing great opportunities for work and society. However, the consequences of technology on the relational dimensions of work are varied and can create opportunities and constraints in supporting coworker relationships (e.g., Parker & Grote, 2020) that may affect work performance. The purpose of this study is to examine how social support can impact work performance in the context of digital services. More specifically, this study aims to understand (1) the effect of social support on work engagement; (2) the effect of social support on task performance and contextual performance; and (3) the mediating role of work engagement in the relationship between social support and task performance and contextual performance. The cross-sectional data was collected from an online questionnaire from 261 workers of different Portuguese enterprises in the digital services sector (e.g., digital marketing, e-commerce, software developers, social media). Social support was accessed through three items from the scale developed by Bakker and Bal (2010). Work engagement was accessed through a short version of nine items of the Utrecht Work Engagement Scale in its Portuguese version for Portugal (Sinval & Marôco, 2020). Task performance was measured through five items, and contextual performance was measured through eight items based on the Individual Work Performance Questionnaire (Ramos-Villagrasa et al., 2019). Using regression analysis, this study examined the contribution of demographic and social support variables to the prediction of work engagement, task, and contextual performance among workers who were working in three work modalities: onsite work, hybrid work, and telework. Work engagement was analyzed as a mediator of that relationship between social support and task and contextual performance. The results revealed that social support accounted for the prediction of work engagement as well as task and contextual performance. Social support was directly and indirectly associated with task and contextual performance through work engagement. This study has certain limitations. Particularly, data were obtained at a single time and from a single source, which may cause a bias due to common-method variance (Podsakoff et al., 2003). Future research could solve this issue by evaluating a model at two or more time points, including validation from other rating sources. Generalizing the results obtained to the population must also be done cautiously, given that we used a convenience sample (i.e., a non-probabilistic sample). In future studies, probabilistic sampling techniques can avoid this selection bias and use longitudinal panel data further to explore the relations between these variables under study. Findings from the study suggest that enhancing social support can be a potential strategy to foster work engagement and improve task and contextual performance outcomes in a digitalized working environment. The results of the present study are relevant because they emphasize that people-centered work principles should be applied in a digitalized working environment. Furthermore, it exposes that uncovering and developing new opportunities for human relationships within digital working situations becomes critical. This study contributes to the debate on the digitalized workplace, working arrangements, and relational aspects of work.